Pharmacokinetics of lamivudine in subjects receiving peritoneal dialysis in end-stage renal failure - Asari, Ashwin (Blackwell Science Inc, 2007)
AIMS: To establish whether peritoneal dialysis (PD) requires dosing modification from the CL(CR)-corrected lamivudine dose in end-stage renal failure subjects. METHODS: This was an open-label cohort study. A total of 12 subjects undergoing PD, six continuous ambulatory peritoneal dialysis (CAPD) and six automated peritoneal dialysis (APD), for at least 3 months received lamivudine 10 mg (5 mg ml (−1) × 2 ml) daily for 8 consecutive days, followed by an intensive pharmacokinetic assessment. Urine and dialysate were collected from 0 to 24 h postdose on day 8 where possible. Pharmacokinetic parameters were calculated using noncompartmental techniques. RESULTS: The plasma pharmacokinetic results demonstrated that peritoneal dialysis clearance (CL(D)) of lamivudine was similar between APD and CAPD patients with median (range) of 0.19 l h(−1) (0.14–0.25) and 0.1 l h(−1) (0.09–0.25), respectively. CL(D) was approximately 1/15th to 1/30th of plasma clearance, demonstrating that peritoneal dialysis does not contribute significantly to overall lamivudine clearance in this patient population. The AUC(0,24 h) of lamivudine given 10 mg daily to APD and CAPD patients was 3430 ng ml(−1) h and 3469 ng ml(−1) h, respectively, similar to historical data obtained in patients with normal renal function administered at the normal dose of 100 mg daily (3781 ng ml(−1) h). There were no clinically significant changes in any safety assessments that were attributable to lamivudine. CONCLUSIONS: ESRD patients who receive CAPD or APD require no supplemental dosing. These patients should follow the standard dosing reduction for patients infected with HIV or HBV with renal dysfunction.